Analytical Profile of Antiviral Drugs-Remdesivir, Simeprevir, and Sofosbuvir: A Review - Eswarudu, M.M.; Krishna, P. Siva; Babu, P. Srinivasa; Sri, G. Ramya; Sravya, K.; Vikhil, J. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Remdesivir (RDV) is an antiviral drug and a phosphonamidite prodrug designed to have activity against a broad spectrum of viruses, act as a nucleoside analogue, and inhibit the RNA-dependent RNA polymerase [RDRP] of coronaviruses, including SARS-CoV-2, whereas Simeprevir (SMV) and Sofosbuvir (SFS) are direct-acting antiviral drugs approved for the treatment of chronic Hepatitis C virus (HCV) infection. Reports show that the structure and replication mechanism of HCV and SARS-COV-2 are comparable. Hepatitis C virus protease inhibitors include Simeprevir. Because it is an NS3/4A protease inhibitor, it inhibits protein synthesis, which stops viruses from maturing. A nucleotide analogue inhibitor called sofosbuvir selectively blocks the RNA-dependent RNA polymerase of HCV NS5B (non-structural protein 5B). This review article gathers and discusses the range of analytical techniques—UV, HPLC, and hyphenated procedures like LC-MS—that are available in the literature for the determination of RDV, SMV, and SFS. This review article can be effectively explored to conduct future analytical investigation for the estimation of the selected drugs in pharmaceutical and biological samples.